2002
DOI: 10.1021/bi012152s
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Membrane Domain of the Human Liver Sodium/Bile Acid Cotransporter

Abstract: Mammalian sodium/bile acid cotransporters (SBATs) are glycoproteins with an exoplasmic N-terminus, an odd number of transmembrane regions, and a cytoplasmic C-terminus. Various algorithms predict eight or nine membrane-embedded regions derived from nine hydrophobic stretches of the protein (H1-H9). Three methods were used to define which of these were transmembrane or membrane-associated segments in the liver bile acid transporter. The first was in vitro translation/insertion scanning using either single hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 26 publications
2
52
0
Order By: Relevance
“…If cholestasis persists, the liver will be damaged and serum bile salts will raise followed by an increase of plasma liver enzymes as a consequence of liver injury. In order to lower or prevent the toxicity of the retained bile salts, The structure of Ntcp has not yet been resolved, but experimental evidence derived from translation/insertion scanning, alanine insertion scanning and mutation of putative N-linked glycosylation site provides evidence for nine transmembrane spanning domains [108], which was later refined to seven transmembrane spanning domains and helices 7 and 8 forming an extracellular loop at the plasma membrane. This loop is essential for function [207].…”
Section: Physiology Of Bile Formationmentioning
confidence: 99%
“…If cholestasis persists, the liver will be damaged and serum bile salts will raise followed by an increase of plasma liver enzymes as a consequence of liver injury. In order to lower or prevent the toxicity of the retained bile salts, The structure of Ntcp has not yet been resolved, but experimental evidence derived from translation/insertion scanning, alanine insertion scanning and mutation of putative N-linked glycosylation site provides evidence for nine transmembrane spanning domains [108], which was later refined to seven transmembrane spanning domains and helices 7 and 8 forming an extracellular loop at the plasma membrane. This loop is essential for function [207].…”
Section: Physiology Of Bile Formationmentioning
confidence: 99%
“…Membrane insertion and sorting of NTCP and ASBT Based on bioinformatic predictions and experimental data, it has been shown that NTCP and ASBT have an extracellular N-terminus, an odd number of transmembrane helices (seven or nine) and a cytoplasmic Cterminus (Hagenbuch et al 1991;Hagenbuch and Meier 1994;Stieger et al 1994;Dawson and Oelkers 1995;Hallén et al 1999;Hallén et al 2002b;Zhang et al 2004). Several potential N-glycosylation sites are present in NTCP, ASBT and SOAT proteins, and site-directed mutagenesis has revealed that only N 5 and N 11 in rat Ntcp (Hagenbuch 1997), and N 10 in human ASBT (Zhang et al 2004) are glycosylated.…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
“…Using N-glycosylation-scanning mutagenesis, Zhang and coworkers strongly suggested a model with seven transmembrane domains for human ASBT (Zhang et al 2004). In contrast, a nine-transmembrane domain arrangement was found by Hallén and coworkers for human ASBT and NTCP (Hallén et al 1999(Hallén et al , 2000(Hallén et al , 2002b. However, it remains unclear whether all of these nine transmembrane segments cross the membrane or whether two of them fold as lipidburied re-entrance loops in the plasma membrane (Hallén et al 2002b;Zahner et al 2003).…”
Section: Functional Properties and Expression Patterns Of The Individmentioning
confidence: 99%
See 1 more Smart Citation
“…A variation on the nine-TM model, in which the seventh and eighth helices are not membranespanning and associate with the outer surface of the plasma membrane, has also been proposed. [18][19][20][21][22][23] In either case, the residues submitted to mutational analysis in this study were mapped in the N-terminal half of a TM segment, viz., the extracellular half of TM3 and the cytosolic half of TM4 in the seven-TM or nine-TM model respectively. Helical wheel projection illustrates y To whom correspondence should be addressed.…”
mentioning
confidence: 99%